«Сплавщик – це було дуже гонорово» (до етнографії лісосплаву на Гуцульщині) - Бідношия, Ю. (Народна творчість та етнологія, 2013)
До 1970-х років лісосплав відігравав важливу роль у господарському житті гуцулів, як і інших груп населення Українських Карпат. У матеріалі пропонуємо наративи керманича із 30-річним стажем Гаврила Крамара із с. Білоберізка Верховинського р-ну Івано-Франківської обл. та Ганни Бельмеги, дочки сплавщика з с. Устеріки того ж району. Спогади про лісосплав представлено на ширшому соціально-побутовому тлі 1940–1970-х років: повстанський рух, життя колгоспників, заборона школярам відвідувати церкву тощо. У текстах збережено діалектні та усномовні особливості. Додано глосарій з місцевих термінів лісосплаву та незрозумілих для широкого кола читачів діалектних слів. Until the 1970s, rafting played an important role in the economic life of the Hutsuls, as well as other groups of the Ukrainian Carpathian population. In the paper, we bring forward the narratives of Havrylo Kramar, a 30-year-experienced timber floater from Biloberizka village (Verkhovyna District, Ivano-Frankivsk Region), and Hanna Belmeha, a raftsman’s daughter from Usteriky village of the same district. Their reminiscences on rafting are presented against the 1940s–1970s broader social background: insurrectional movement, life of collective farmers, prohibition to schoolchildren from attending church, etc. The dialectal and colloquial expressions are preserved in the texts. A glossary of local rafting vernacular and dialect words unintelligible to a wider audience is attached.